Photosensing properties of ruthenium(II) complex-based photodiode - Imer, Arife Gencer; Dere, Aysegul; Al-Sehemi, Abdullah G.; Dayan, Osman; Serbetci, Zafer; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2019)
Ru(II) complex containing 2,6-di(1H-pyrazol-3-yl)pyridine ligand was synthesized to prepare organic-based photodiode. After forming the back contact with aluminum metal on p-Si by thermal evaporation, Al/Ru(II) complex/p-Si heterojunction was constructed by inserting Ru(II) complex organic layer into Si substrate. The fundamental electrical parameters and photosensing properties of fabricated heterojunction were investigated by current-voltage and capacitance-voltage measurements under the dark and different light intensities. The studied device exhibits a good rectifying property with rectification ratio of 2.4x10(4) at +/- 7V. It is observed that the photosensing properties such as light sensitivity and photoconductive responsivity of the photodiode based on Ru(II) complex are strongly dependent on the illumination power. The transient measurements show that the heterojunction device has a good photo switching property in the application of the photodiode, photoconductor and photocapacitor. The obtained results declare that the fabricated Ru(II)-based heterojunction device can be used in the organic-based optoelectronic device applications as a photodiode, photosensor, and optical sensor.
Keywords: Ru(Ii) Complexes; Transfer Hydrogenation; Photoelectrical Characterization; Electrical Characteristics; Ligands; Diode; Tridentate; Parameters; Behavior; Junction